Analysis of Influencing Factors and Volatility of Broiler Meat Prices in Pasuruan Regency, East Java Province - Hariadi Subagja; Durrotun Nikmah (Buletin Peternakan, 2020)
The research was aimed to analyze of broiler meat price fluctuation, identify the factors competitor foodstuffs price that influence of broiler meat price, and identify alternative foodstuffs of broiler meat at consumer level in Pasuruan. The determination of location was did deliberately with consideration that in 2013, the production of broiler meat in Pasuruan was fourth highest production after Malang, Sidoarjo and Jombang , it was 8,842 million kg. This research was used secondary data from January 2010 until November 2015. The analytical method used is the price volatilitass analysis and multiple linear regression. The results showed that the value of broiler meat price volatility in Pasuruan tend to be small (low volatility) and happen quickly. Factors competitor foodstuffs price that influence the price of broiler meat in Pasuruan simultaneously influenced by the price of local chicken meat, beef prices, the price of eggs, and prices of salted anchovies fish. While partially, broiler meat prices at the consumer level in Pasuruan influenced by the price of beef and the price of eggs. The relation between the both showed that: broiler meat is alternative foodstuffs for beef, eggs are alternative foodstuffs for meat broiler, salted anchovies fish is complements for broiler meat.